Hierarchical Intra-modal Correlation Learning for Label-free 3D Semantic Segmentation - Kang, Xin; Chu, Lei; Li, Jiahao; Chen, Xuejin; Lu, Yan (The IEEE/CVF Conference on Computer Vision and Pattern Recognition 2024, 2024)
Recent methods for label-free 3D semantic segmentation aim to assist 3D model training by leveraging the open-world recognition ability of pre-trained vision language models. However, these methods usually suffer from inconsistent and noisy pseudo-labels provided by the vision language models. To address this issue, we present a hierarchical intra-modal correlation learning framework that captures visual and geometric correlations in 3D scenes at three levels: intra-set, intra-scene, and inter-scene, to help learn more compact 3D representations. We refine pseudo-labels using intra-set correlations within each geometric consistency set and align features of visually and geometrically similar points using intra-scene and inter-scene correlation learning. We also introduce a feedback mechanism to distill the correlation learning capability into the 3D model. Experiments on both indoor and outdoor datasets show the superiority of our method. We achieve a state-of-the-art 36.6% mIoU on the ScanNet dataset, and a 23.0% mIoU on the nuScenes dataset, with improvements of 7.8% mIoU and 2.2% mIoU compared with previous SOTA. We also provide theoretical analysis and qualitative visualization results to discuss the mechanism and conduct thorough ablation studies to support the effectiveness of our framework.